Sura of Al-Takwir Argument study - Ne'ma Nghimsh, Ammar (Journal of College of Education, 2020)
This research examines modern theory and applies it to a Quranic script that is characterized by abysmal levels that aim at presenting the argument to the polytheists who opposed the Prophet (pbh) and the revelation. It is added that the Sura was divided into three scenes, and the latter includes a set of authentic factors that make the reader pay attention to the dialogue presented by the Qur’anic text to convince the interviewer .